William Smithson papers - Smithson, William
Powers of attorney and other legal documents.
Merchant, of Leeds, England, and later of New York, N.Y.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Merchants -- England -- Leeds; Merchants -- New York (State) -- New York; Power of attorney -- Great Britain; Power of attorney -- United States; Merchants